Effect of Auxins on Rooting Stem Cuttings of Givotia Rottleriformis Griff. via Hydropit - Babitha, M.; Rao, P. S.; Meru, Elusing; Sreenivasulu, A. (Indian Forester, 2002)
An experiment was conducted on the effect of auxins on rooting stem cuttings of Givotia rottleriformis at Srinivasavanam Field Research Station, Tirupati. Three different hormones (IAA,IBA and NAA) were tried with 4 different concentrations (500,1000,3000 and 5000 ppm). Rooting was observed after 45 days in all the treated cuttings. IBA 3000 ppm treated cuttings showed highest rooting percentage (77.8) and it was at par with IBA 5000 ppm and differs significantly from others. IAA 500 ppm treated cuttings showed least rooting percentage (33.3). No rooting was observed in control.